Studies on Corrosion of Annealed and Aged 18 Ni 250 Grade Maraging Steel in Sulphuric Acid Medium - Poornima,T. (2010)
The corrosion behavior of aged and annealed sample of 18 Ni 250 grade maraging steel was investigated in varied conditions of concentration and temperature of sulphuric acid medium, using electrochemical techniques like Tafel polarization and electrochemical impedance spectroscopy (EIS). The results obtained from both the techniques are in good agreement. These results have shown increase in corrosion rate of aged specimen with increase in concentration and temperature of sulphuric acid. With increase in concentration of sulphuric acid from 0.025 M to 0.25 M the corrosion rate of annealed sample was found to increase, but there after in 0.5 M, 0.75 M and 1 M, the rate of corrosion decreases, indicating passivation of alloy surface at higher concentration of sulphuric acid. The corrosion rate of aged specimen was found to be higher than that of the annealed specimen. Similar observations are revealed by SEM images. The thermodynamic parameters like activation energy, enthalpy of activation and entropy of activation were calculated.